Herpes simplex virus type 2 seroprevalence and associated factors in fertility-treatment-seeking population: A cross-sectional survey in the United Arab Emirates - Abdo, Noor Motea; Aslam, Irfan; Irfan, Shazia; George, Junu A.; Alsuwaidi, Ahmed R.; Ahmed, Luai A.; Al-Rifai, Rami H. (Frontiers in Public Health, 2022)
Background: Herpes simplex virus type 2 (HSV-2) is a common genital infection affecting more than 400 million individuals globally. In the United Arab Emirates (UAE), in specific at-risk population groups, the burden of HSV-2 has not been reported. This study investigated the prevalence of HSV-2 IgG antibodies in patients seeking fertility treatment and characterized patients with seropositivity to HSV-2 IgG antibodies. Methodology: A cross-sectional sample of patients seeking fertility treatment in a major fertility clinic in Abu Dhabi, UAE was surveyed from April to May 2021. Patients were consecutively invited to complete self-administered questionnaires and provide blood for HSV-2 testing. Information on sociodemographics, medical history, and infertility was collected. Serum specimens were screened using an enzyme-linked immunosorbent assay for HSV-2 IgG antibodies detection. Results: Two hundred and ninety-nine patients were surveyed and provided blood samples. The mean age of the patients was 35.9 ± 6.8 (mean ± standard deviation [SD]) years with 89.3% being women. Sixty-six percent were overweight or obese, 25.0% had at least one chronic comorbidity, and 19.6% reported ever-had genital infection. More than two-thirds (68.3%) of the patients were infertile for ≥ 6 months. Of the 42 infertile males, 69.0% had an abnormal semen analysis. HSV-2 IgG antibodies was detected in 12.4% of patients. The HSV-2 IgG antibodies in seropositive patients had a higher mean age (39.5 versus 35.4 years; p < 0.001) compared to seronegative patients. HSV-2 IgG antibodies seropositivity was more common in males (15.6%) than females (12.0%), in patients with secondary (14.1%) versus primary (9.2%) infertility, or in males with abnormal (10.3%) versus normal (7.7%) semen. Conclusion: Exposure to HSV-2 at any time in patients seeking fertility treatment in the UAE was found to be slightly common in more than one out of 10 patients. Tailored health campaigns on HSV-2 prevention are warranted.